Prospective Investigation of Feline Leukemia Virus Infection in Stray Cats Subjected to a Trap–Neuter–Return Program in Switzerland - Marina L. Meli; Benita Pineroli; Esther Geisser; Regina Hofmann-Lehmann (Viruses, 2024)
Feline leukemia virus (FeLV) remains a serious concern in some countries despite advances in diagnostics and vaccines. FeLV-infected cats often have reduced lifespans due to FeLV-associated diseases. The infection is transmitted through social interactions. While Northern European countries have reported a decrease in FeLV among pet cats, Switzerland’s rates remain stagnant at 2.7% (2016/17: 95% CI 1.4–5.2%). Research on FeLV in Swiss stray cats has been lacking, even though these animals could serve as a virus reservoir. Sampling stray cats that do not receive regular veterinary care can be challenging. Collaboration with the Swiss Network for Animal Protection (NetAP) allowed for the prospective collection of saliva samples from 1711 stray cats during a trap–neuter–return program from 2019 to 2023. These samples were tested for FeLV RNA using RT-qPCR as a measure for antigenemia. Viral RNA was detected in 4.0% (95% CI 3.1–5.0%) of the samples, with 7.7% (95% CI 4.9–11.3%) in sick cats and 3.3% (95% CI 2.4–4.4%) in healthy ones. We identified three geographically independent hotspots with alarmingly high FeLV infection rates in stray cats (up to 70%). Overall, including the previous data of privately owned cats, FeLV-positive cats were scattered throughout Switzerland in 24/26 cantons. Our findings underscore welfare concerns for FeLV infections among stray cats lacking veterinary attention, highlighting the potential risk of infection to other free-roaming cats, including those privately owned. This emphasizes the critical significance of vaccinating all cats with outdoor access against FeLV and developing programs to protect cats from FeLV infections.